Humor as a Communicative Style in Social Media - Mahmud, Murni; Halim, Abdul; Burhamzah, Muftihaturrahmah (Seminar Nasional LP2M UNM, 2024)
Social media has been growing so fast in todays’ society and its roles bear either advantages or disadvantages for people. As a setting of communication both verbal and nonverbal communication, social media provides various styles in communicating and entertaining. One of them is the use of humor. This research focuses on the phenomena of the use of humor as a communicative style in social media. Therefore, this research is formulated to find out the kinds of humor used by in social media. This research is qualitative applying the technique of Discourse Analysis covering data collection, data selection, data analysis, and data report. This paper took one kind of social media that is very popular, namely Instagram. The data was obtained from Fadil Jaidi's video transcript which was accessed from Instagram, and the data is analyzed by observing. The theory used in this research article is Shade's (1996) classification of humor: namely figural humor, verbal humor, visual humor, and auditory humor. Of the four types of humor, the author's focus in this study is visual humor (jokes, puns, riddles, satire, parody, irony, wit, limerick, farce, sarcasm, tall tale. Findings from this research shows that the most widely used type of humor is sarcasm humor. Sarcasm humor is a type of humor that is done by saying a sentence that can offend someone but uses a joking tone so that it can invite laughter from the listeners of the humor. Keywords: humor; social media; communication; communicative styles